High-quality stiffener with excellent bending resistance
Patent Information
- Application Number
- JP2020042959
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-03-12
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2040-03-12
AI Technical Summary
【0010】 スティフナー中に欠点があると、その部分に応力が集中し、割れ、欠けなどの原因となる。また、一般にFPC基板に要求される耐熱性は半田付け温度を想定すれば260℃程度であり、さらに内燃機関、外燃機関、核エネルギー施設、航空宇宙用途、地殻掘削機器、金属産業などの現場で用いられる機器にはさらに高い温度での長時間にわたる耐熱性が要求される。これらの高温下においては、熱的、機械的ストレスがスティフナーにかかるため、室温での使用よりもスティフナー中の欠陥が少ないことが重要である。 本発明におけるスティフナーは、構成するポリイミドフィルムが単層、複層のいずれの場合であっても、欠点が少ないスティフナーに関する。また、本発明におけるスティフナーはコネクタなどの部品との接触部における耐折り曲げ性を有するため、高温領域において使用されるFPC基板の部分的な補強、たとえばコネクタ抜き差し部分の補強に好ましく用いられる。
Smart Images

Figure 0007651824000002 
Figure 0007651824000003 
Figure 0007651824000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a stiffener (support plate or reinforcing plate) that is adhered to a flexible printed circuit board (hereinafter referred to as "FPC board") in order to maintain the strength of the FPC board, and in particular to a polyimide film laminate stiffener formed by bonding multiple polyimide films together with an adhesive. [Background technology]
[0002] Representative examples of films in which a heat-curing adhesive is applied to one or both sides of a single-layer or multi-layer polyimide film include "coverlay films" and "films for TAB (Tape Automated Bonding)". The adhesive used in these films is applied to a substrate film 11 made of a polyimide film, as shown in FIG. 1(a), and then dried to form a semi-cured (B-stage) adhesive layer 12. A separator 13 is usually further laminated on the surface of this adhesive layer 12. This laminate is stored in a form having an adhesive layer in a semi-cured state before use. Another form of adhesive layer for polyimide film is a prepreg obtained by impregnating a reinforcing substrate such as glass cloth with an adhesive varnish and drying it. The adhesive in the prepreg is also stored in a B-stage state. 1(b), the base film 11 of these coverlay films or TAB films is superimposed on an object such as an FPC board 14 via an adhesive layer 2 (made of an adhesive or prepreg), and heated and pressed, so that the base film 11 is bonded to the object such as an FPC board 14. Also, as shown in FIG. 2, an FPC board in which a metal foil 23 such as copper foil and a polyimide film 11 are bonded with an adhesive 22 is known, but in these bondings, heat aging is required after the metal foil and the polyimide film are laminated together.
[0003] Incidentally, FPC boards are usually thin (for example, 12.5 to 100 μm). However, when the board is thin, problems are likely to occur in the switch section and connector section. For this reason, as shown in FIG. 3, FPC boards made of polyimide film including the parts where the problems are likely to occur or parts where the problems are likely to occur are conventionally fixed to a support such as a stiffener via a heat-curing adhesive (called a bonding sheet). In this case, the general bonding conditions are heating and pressurizing at 150 to 180° C. for 15 to 45 minutes under a pressure of 1 to 3 MPa. A single-layer polyimide film is generally used as a stiffener used to support or reinforce this FPC board. Single-layer polyimide films with a thickness of 225 μm or less are widely and generally available on the market, and these commercially available single-layer polyimide films are used as stiffeners. Representative examples of these single-layer polyimide films include polyimide films sold under the trade names Kapton H or V type (manufactured by DuPont Toray Co., Ltd.), Upilex S type (manufactured by Ube Industries, Ltd.), and Apical AH or NPI type (manufactured by Kaneka Corporation). Single-layer polyimide films have a consistent hardness and stiffness depending on the product. However, depending on the application, there are cases where a film of the same thickness is required to have greater rigidity than a single-layer film.
[0004] Furthermore, polyimide films are mainly produced by solution casting, and due to this manufacturing process it is difficult to produce thick films, and the productivity is extremely poor.
[0005] For this reason, a sheet made by laminating multiple polyimide films is sometimes used as a stiffener, but if foreign matter gets caught between the films when laminating multiple films, if there is insufficient pressure when laminating, if there are gaps such as blisters due to convexities on the film surface, etc., the strength of the stiffener becomes insufficient in those areas. Even in the case of a single-layer stiffener, the strength may be insufficient if there are gaps or scratches that occur during film formation.
[0006] In addition, since stiffeners are often used together with metal parts that are more rigid than polyimide films, bending resistance at the joints with the hard members is important.
[0007] Any gaps, scratches, or foreign objects caught in the bent parts can cause cracks. DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0008] As a result of intensive research to solve the above problems, the inventors conducted compression tests on stiffeners using rods and found that if the number of parts not satisfying certain conditions is 0.1 / cm2 or less, the stiffener has few defects and is strong enough for FPCs. Furthermore, they found that if the difference in strain at the breaking point when the compression test speed is changed from 0.2mm / min to 10mm / min is 15% or less at 0.2mm / min, the stiffener has excellent resistance to 90-degree bending and is unlikely to leave a crease at the contact point with a metal part. [Means for solving the problem]
[0009] That is, the present invention comprises the following: [1] A stiffener made of a polyimide film, A stiffener characterized in that when a compression test in the thickness direction is conducted at a compression speed of 0.2 mm / min using a rod with a contact surface of 10 mm x 10 mm, the number of areas that do not satisfy the following condition (I) is 0.1 or less per square centimeter. Condition (I) In a stress-strain curve of the stiffener, obtained by plotting compressive strain on the horizontal axis and compressive stress on the vertical axis, the strain value at the transition point where the stress-strain curve starts to transition to a linear region is 20% or less of the stiffener thickness. [2] The stiffener according to [1] above, characterized in that when a compression test is conducted in the thickness direction using a rod having a contact surface with the stiffener of 10 mm x 10 mm, the stiffener satisfies the following condition (II): Condition (II) In the stress-strain curve of the stiffener, obtained with the compression speeds of 10 mm / min and 0.2 mm / min, the horizontal axis is the compressive strain and the vertical axis is the compressive stress, the compressive stress σ at the strain where the stress is maximum 10 and σ 0.2 The difference is |σ 10- σ 0.2 |<0.15×σ 0.2 It is. [3] The stiffener according to [1] above, characterized in that no cracks are generated in the bent portion when the stiffener is bent at a 60° angle along an iron plate placed on top, held for 3 seconds, and released, 10 times. Effect of the Invention
[0010] If there is a defect in the stiffener, stress will concentrate in that area, causing cracks, chipping, etc. In addition, the heat resistance generally required for FPC boards is about 260°C assuming soldering temperatures, and even higher temperatures and long-term heat resistance are required for equipment used in internal combustion engines, external combustion engines, nuclear energy facilities, aerospace applications, earth drilling equipment, metal industry, and other on-site applications. At these high temperatures, thermal and mechanical stress is applied to the stiffener, so it is important that there are fewer defects in the stiffener than when used at room temperature. The stiffener of the present invention has few defects whether the constituent polyimide film is a single layer or multiple layers. In addition, since the stiffener of the present invention has bending resistance at the contact portion with a component such as a connector, it is preferably used for partial reinforcement of an FPC board used in a high temperature region, for example, reinforcement of a connector insertion / removal portion. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic cross-sectional view of (a) a PI film having an adhesive layer on one side and (b) an FPC board to which the PI film is bonded. [Diagram 2] Figure 2 is a schematic cross-sectional view of an FPC board made by bonding copper foil and a PI film. [Diagram 3] Figure 3 is a schematic cross-sectional view of a stiffener made by bonding two thin PI films together. [Figure 4] FIG. 4 is a schematic diagram of a stiffener bending test in the present invention. [Diagram 5] FIG. 5 is a schematic diagram showing an example of an apparatus used in the method of treating a film with a silane coupling agent via a gas phase in the present invention. [Figure 6] FIG. 6 is a schematic diagram showing an example of an apparatus used in the method of treating a film with a silane coupling agent via a gas phase in the present invention. [Figure 7] FIG. 7 shows an example of a typical compressive stress-strain curve that leads to fracture without showing a yield point. [Figure 8] FIG. 8 shows an example of a typical compressive stress-strain curve where a yield point appears. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] <Shape of stiffener> The stiffener in the present invention is a reinforcing material made of resin, and the shape is not particularly limited. For example, the shape of the upper surface may be a square, a rectangle, a circle, etc. Furthermore, the number of layers may be any number, and it may be a single layer of resin film.
[0013] <Polyimide film lamination method> The polyimide film constituting the stiffener in the present invention may be a single layer, or multiple polyimide films may be laminated. Methods for laminating polyimide films include a method of laminating by hot pressing using a thermoplastic resin as an adhesive, a method of applying a reactive liquid such as a silane coupling agent to the bonding surfaces and laminating them, and a method of subjecting the polyimide film surface to an easy-to-adhere treatment such as plasma treatment and then hot pressing.
[0014] <Silane coupling agent> The silane coupling agent in the present invention refers to a compound that has a silicon element in its molecule, and acts to physically and chemically mediate between polyimide films and increase the adhesive strength between them. Preferred specific examples of the silane coupling agent include N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3 -Glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, p-styryltrimethoxysilane, 3-methacryloxy Propylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane hydrochloride, 3-ureidopropyltriethoxysilane, 3-chloropropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, bis(triethoxysilylpropyl)tetrasulfide, 3-isocyanatepropyltriethoxysilane, tris-(3-trimethoxysilylpropyl)isocyanurate, chloromethylphenethyltrimethoxysilane, chloromethyltrimethoxysilane, aminophenyltrimethoxysilane, aminophenethyltrimethoxysilane, aminophenylaminomethylphenethyltrimethoxysilane, hexamethyldisilazane, and the like.
[0015] In addition to the above, examples of the silane coupling agent that can be used in the present invention include n-propyltrimethoxysilane, butyltrichlorosilane, 2-cyanoethyltriethoxysilane, cyclohexyltrichlorosilane, decyltrichlorosilane, diacetoxydimethylsilane, diethoxydimethylsilane, dimethoxydimethylsilane, dimethoxydiphenylsilane, dimethoxymethylphenylsilane, dodecyltrichlorosilane, dodecyltrimethoxysilane, ethyltrichlorosilane, hexyltrimethoxysilane, octadecyltriethoxysilane, octadecyltrimethoxysilane, n-octyltrichlorosilane, n-octyltriethoxysilane, n-octyltrimethoxysilane, triethoxyethylsilane, triethoxymethylsilane, trimethoxymethylsilane, trimethoxyphenylsilane, nylsilane, pentyltriethoxysilane, pentyltrichlorosilane, triacetoxymethylsilane, trichlorohexylsilane, trichloromethylsilane, trichlorooctadecylsilane, trichloropropylsilane, trichlorotetradecylsilane, trimethoxypropylsilane, allyltrichlorosilane, allyltriethoxysilane, allyltrimethoxysilane, diethoxymethylvinylsilane, dimethoxymethylvinylsilane, trichlorovinylsilane, triethoxyvinylsilane, vinyltris(2-methoxyethoxy)silane, trichloro-2-cyanoethylsilane, diethoxy(3-glycidyloxypropyl)methylsilane, 3-glycidyloxypropyl(dimethoxy)methylsilane, 3-glycidyloxypropyltrimethoxysilane, and the like can also be used.
[0016] In addition, other alkoxysilanes, such as tetramethoxysilane and tetraethoxysilane, may be appropriately added to the silane coupling agent.
[0017] In addition, when other alkoxysilanes such as tetramethoxysilane, tetraethoxysilane, etc. are appropriately added to the silane coupling agent, or when they are not added, the reaction may be slightly advanced by mixing and heating before use.
[0018] Among such silane coupling agents, the silane coupling agent preferably used in the present invention is preferably a silane coupling agent having a chemical structure having one silicon atom per molecule. In the present invention, particularly preferred silane coupling agents include N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, aminophenyltrimethoxysilane, aminophenethyltrimethoxysilane, aminophenylaminomethylphenethyltrimethoxysilane, etc. When particularly high heat resistance is required in the process, it is desirable to use an aromatic group connecting Si and the amino group. In the present invention, a phosphorus-based coupling agent, a titanate-based coupling agent, etc. may be used in combination, if necessary.
[0019] <Silane coupling agent treatment> Generally, the silane coupling agent treatment refers to a treatment for forming a thin film layer made of a silane coupling agent or a condensation product of a silane coupling agent on the surface of an object. Silane coupling agent treatment generally involves preparing a solution of the silane coupling agent in an alcohol or the like, applying it to the object or immersing the object in the silane coupling agent solution, and then drying and heating the silane coupling agent to condense and simultaneously bond it to the surface of the object through a chemical reaction. Common methods for applying the silane coupling agent include spin coating, spray coating, capillary coating, and dipping. The silane coupling agent treatment is carried out on one or both sides of the polyimide film as required.
[0020] In the present invention, the silane coupling agent application step can be preferably carried out via a gas phase. Dissolving the gas phase is a method of exposing the polyimide film to a vaporized silane coupling agent. Vaporization refers to a state in which the vapor of the silane coupling agent, that is, the silane coupling agent in a substantially gaseous state or the silane coupling agent in a fine particle state, exists. And, exposure to this refers to contacting the polyimide film with an atmosphere containing the vaporized silane coupling agent. Since the silane coupling agent has a certain vapor pressure, a certain amount of the silane coupling agent in a gaseous state exists even in a room temperature atmosphere. If the liquid silane coupling agent is heated to a temperature of 40°C to the boiling point of the silane coupling agent, a vapor of the silane coupling agent with a higher concentration can be obtained. The vaporized silane coupling agent may be misted due to the dew point relationship and exist in a fine particle state in the gas. In the present invention, such a state can also be used. In addition, an operation to increase the vapor density by manipulating the temperature and pressure can be added. The boiling point of the silane coupling agent varies depending on the chemical structure, but is generally in the range of 100 to 250° C. However, heating to 200° C. or higher is not preferable because it may cause a side reaction on the organic group side of the silane coupling agent. The environment in which the silane coupling agent is heated may be under pressure, approximately normal pressure, or reduced pressure, but in order to promote the vaporization of the silane coupling agent, approximately normal pressure or reduced pressure is preferable. Since most silane coupling agents are flammable liquids, it is preferable to carry out the vaporization work in a sealed container, preferably after replacing the inside of the container with an inert gas. However, from the viewpoint of improving production efficiency and reducing the cost of production equipment, it is preferable to apply the silane coupling agent in an environment without a vacuum. The silane coupling agent deposition method of the present invention without a vacuum does not mean that a vacuum is not used only during deposition, but that the deposition is carried out under approximately atmospheric pressure from setting a polyimide film in a normal atmospheric atmosphere, replacing it with a carrier gas to deposit the silane coupling agent, and then returning to a state without the silane coupling agent. The time for exposing the polyimide film to the silane coupling agent is not particularly limited, but is within 60 minutes, preferably within 20 minutes, and more preferably within 10 minutes. The exposure time is a process design value determined by the relationship between the concentration of the silane coupling agent and the required amount of the silane coupling agent to be applied. The lower limit of the exposure time is not particularly limited, but in order to reduce unevenness in the amount of application that occurs industrially, it is better to set the time to 10 seconds or more, preferably 30 seconds or more.
[0021] The temperature of the polyimide film during exposure to the silane coupling agent is preferably controlled to an appropriate temperature between -50°C and 200°C depending on the type of silane coupling agent and the desired thickness of the silane coupling agent layer. The polyimide film exposed to the silane coupling agent is preferably heated to 70°C to 200°C, more preferably 75°C to 150°C after exposure. This heating causes the hydroxyl groups on the surface of the polyimide film to react with the alkoxy groups or silazane groups of the silane coupling agent, completing the silane coupling agent treatment. The heating time is 10 seconds to 10 minutes. If the temperature is too high or the time is too long, the coupling agent may deteriorate. If the time is too short, the treatment effect cannot be obtained. If the temperature of the substrate during exposure to the silane coupling agent is already 80°C or higher, the subsequent heating can be omitted.
[0022] In the present invention, it is preferable to hold the silane coupling agent-coated surface of the polyimide film facing downward and expose it to the silane coupling agent vapor. In the conventional method of applying a solution of a silane coupling agent, the coated surface of the polyimide film inevitably faces upward during and before and after application, so that the possibility of floating foreign matter in the working environment being deposited on the inorganic substrate surface cannot be denied. However, in the present invention, the polyimide film can be held facing downward. It is possible to greatly reduce the adhesion of foreign matter in the environment. In addition, when introducing a gas containing vaporized silane coupling agent into a chamber in which the polymer substrate is exposed, it is also effective to first separate the gas into two or more gases and then introduce them, or to cause two or more gases to collide in the chamber to generate turbulence and uniformly distribute the silane coupling agent. As a method for vaporizing the silane coupling agent, in addition to evaporation by heating, there is also a method of introducing a gas into the silane coupling agent liquid to generate bubbles. This is hereafter called bubbling. Regarding bubbling, it is effective to simply place a pipe through which gas passes into the silane coupling agent liquid, to attach a porous body to the end of the pipe so that many fine bubbles are generated, or to superimpose ultrasonic waves to promote vaporization.
[0023] In addition, the vaporized silane coupling agent may become charged. By utilizing this effect and applying an electric field to the film during exposure, a large amount of silane coupling agent can be deposited in a short time, and since the silane coupling agent has kinetic energy, the deposited film can be prevented from becoming an island-like film. In addition, it is known that if the carrier gas used contains moisture, the moisture will start to react with the silane coupling agent. For this reason, it is effective to have a low dew point. The dew point is preferably 15°C or less, more preferably 10°C or less, and even more preferably 5°C or less. In a preferred embodiment of the present invention, the number of silicon-containing foreign particles having a major axis of 10 μm or more in the silane coupling agent layer of the silane coupling agent layer-laminated polyimide film is 2000 pieces / m2 or less, preferably 1000 pieces / m2 or less, and further 500 pieces / m2 or less. The number of silicon-containing foreign particles can be achieved by combining the above operations.
[0024] The amount of the silane coupling agent applied depends on the thickness of the silane coupling agent condensate layer. If the coupling agent layer is too thick, the amount of decomposition products generated during exposure to high temperatures increases, which may inhibit adhesion between polyimide films. The thickness of the silane coupling agent condensate layer of the present invention is preferably 0.1 nm or more and 300 nm or less, and more preferably 0.5 nm or more and 200 nm or less. Furthermore, the upper limit of the thickness is preferably less than 200 nm, preferably 150 nm or less, and more preferably 100 nm or less for practical use, more preferably 70 nm or less, and even more preferably 50 nm or less. In the region of 0.1 nm or less, it is assumed that the coupling agent is present in clusters rather than as a uniform coating film, which is not preferable. The film thickness of the silane coupling agent condensate layer was determined by polishing a cross section perpendicular to the film surface of the polyimide film laminate, cutting it into ultra-thin slices with a microtome, taking a photograph of the cross section with a transmission electron microscope, and calculating the actual measured value from the magnification.
[0025] The thickness of the polyimide film of the present invention is preferably 3 μm or more, more preferably 11 μm or more. There is no particular upper limit to the thickness of the polyimide film, but it is preferably 250 μm or less, more preferably 150 μm or less, and even more preferably 90 μm or less, in view of the requirements for flexible electronic devices. From the viewpoint of production efficiency and cost of laminates and flexible electronic devices, the area of the polyimide film of the present invention is preferably large, preferably 1000 cm2 or more, more preferably 1500 cm2 or more, and even more preferably 2000 cm2 or more.
[0026] In the present invention, the polyimide film may be made of an aromatic polyimide, an alicyclic polyimide, a polyamideimide, a polyetherimide, etc. More preferably, the polyimide film is made of a polymer containing 50% or more of a polyimide skeleton.
[0027] In general, a polyimide film is obtained by applying a polyamic acid (polyimide precursor) solution obtained by reacting diamines with tetracarboxylic acids in a solvent onto a support for producing a polyimide film, drying the solution to form a green film (also called a "precursor film" or "polyamic acid film"), and then subjecting the green film to high-temperature heat treatment on the support for producing a polyimide film or after being peeled off from the support to cause a dehydration ring-closing reaction.
[0028] The diamines constituting the polyamic acid are not particularly limited, and aromatic diamines, aliphatic diamines, alicyclic diamines, etc., which are usually used in polyimide synthesis, can be used. From the viewpoint of heat resistance, aromatic diamines are preferred, and among aromatic diamines, aromatic diamines having a benzoxazole structure are more preferred. When aromatic diamines having a benzoxazole structure are used, it is possible to develop high heat resistance, high flexural modulus, low thermal shrinkage, and low linear expansion coefficient. The diamines may be used alone or in combination of two or more kinds.
[0029] The aromatic diamines having a benzoxazole structure are not particularly limited, and examples thereof include 5-amino-2-(p-aminophenyl)benzoxazole, 6-amino-2-(p-aminophenyl)benzoxazole, 5-amino-2-(m-aminophenyl)benzoxazole, 6-amino-2-(m-aminophenyl)benzoxazole, 2,2'-p-phenylenebis(5-aminobenzoxazole), 2,2'-p-phenylenebis(6-aminobenzoxazole), 1-(5-aminobenzoxazolo)-4-(6-aminobenzoxazolo)benzene, 2,6-(4,4'-diazomethane)-1,1-diamine, 1,2-diamine, 1,3-diamine, 1,4-diamine, 1,5-diamine, 1,6-diamine, 1,7-diamine, 1,8-diamine, 1,9-diamine, ...4-diamine, 1,5-diamine, 1,6-diamine, 1,4-diamine, 1,5-diamine, 1,6-diamine, 1,7-diamine, 1,8-diamine, 1,9-diamine, 1,1-diamine, 1,2-diamine, 1,4-diamine, 1,5-diamine, 1,4-di 2,6-(4,4'-diaminodiphenyl)benzo[1,2-d:4,5-d']bisoxazole, 2,6-(3,4'-diaminodiphenyl)benzo[1,2-d:5,4-d']bisoxazole, 2,6-(3,4'-diaminodiphenyl)benzo[1,2-d:4,5-d']bisoxazole, 2,6-(3,4'-diaminodiphenyl)benzo[1,2-d:4,5-d']bisoxazole, 2,6-(3,3'-diaminodiphenyl)benzo[1,2-d:5,4-d']bisoxazole, 2,6-(3,3'-diaminodiphenyl)benzo[1,2-d:4,5-d']bisoxazole, and the like.
[0030] Examples of aromatic diamines other than the aromatic diamines having a benzoxazole structure described above include 2,2'-dimethyl-4,4'-diaminobiphenyl, 1,4-bis[2-(4-aminophenyl)-2-propyl]benzene (bisaniline), 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene, 2,2'-ditrifluoromethyl-4,4'-diaminobiphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, bis[4-(3-aminophenoxy)phenyl], ketone, bis[4-(3-aminophenoxy)phenyl]sulfide, bis[4-(3-aminophenoxy)phenyl]sulfone, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, m-phenylenediamine, o-phenylenediamine, p-phenylenediamine, m-aminobenzylamine, p-aminobenzylamine, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, aminodiphenyl ether, 3,3'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfoxide, 3,4'-diaminodiphenyl sulfoxide, 4,4'-diaminodiphenyl sulfoxide, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminobenzophenone, 3,4'-diaminobenzophenone, 4,4'-diaminobenzophenone, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diaminodi Phenylmethane, bis[4-(4-aminophenoxy)phenyl]methane, 1,1-bis[4-(4-aminophenoxy)phenyl]ethane, 1,2-bis[4-(4-aminophenoxy)phenyl]ethane, 1,1-bis[4-(4-aminophenoxy)phenyl]propane, 1,2-bis[4-(4-aminophenoxy)phenyl]propane, 1,3-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 1,1-bis[4-(4-aminophenoxy)phenyl]butane, 1,3-bis[4-(4-aminophenoxy)phenyl]butane, 1,4-bis[4-(4-aminophenoxy)phenyl]butane, 2,2-bis[4-(4-aminophenoxy)phenyl]butane, 2,3-bis[4-(4-aminophenoxy)phenyl]butane, 2-[4-(4-aminophenoxy)phenyl]-2-[4-(4-aminophenoxy)-3-methylphenyl]propane, 2,2-bis[4-(4-aminophenoxy)-3-methylphenyl]propane, 2-[4-(4-aminophenoxy)phenyl]-2-[4-(4-aminophenoxy)phenyl] 1,4-bis(3-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis[4-(4-aminophenoxy)phenyl]ketone, bis[4-(4-aminophenoxy) phenyl]sulfide, bis[4-(4-aminophenoxy)phenyl]sulfoxide, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(4-aminophenoxy)phenyl]ether, 1,3-bis[4-(4-aminophenoxy)benzoyl]benzene, 1,3-bis[4-(3-aminophenoxy)benzoyl]benzene, 1,4-bis[4-(3-aminophenoxy)benzoyl]benzene, 4,4'-bis[(3-aminophenoxy)benzoyl]benzene, 1 ,1-Bis[4-(3-aminophenoxy)phenyl]propane, 1,3-Bis[4-(3-aminophenoxy)phenyl]propane, 3,4'-diaminodiphenyl sulfide, 2,2-Bis[3-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, bis[4-(3-aminophenoxy)phenyl]methane, 1,1-Bis[4-(3-aminophenoxy)phenyl]ethane, 1,2-Bis[4-(3-aminophenoxy)phenyl]ethane, bis[4-(3-aminophenoxy)phenyl]sulfoxide, 4,4'-bis[3-(4-aminophenoxy)benzoyl]diphenyl ether, 4,4'-bis[3-(3-aminophenoxy)benzoyl]diphenyl ether, 4,4'-bis[4-(4-amino-α,α-dimethylbenzyl)phenoxy]benzophenone, 4,4'-bis[4-(4-amino-α,α-dimethylbenzyl)phenoxy]diphenyl sulfone, bis[4-{4-(4-aminophenoxy)phenoxy}phenyl]sulfone, 1,4-bis[4-(4-aminophenoxy)phenoxy-α,α-dimethylbenzyl]benzene, 1, 3-bis[4-(4-aminophenoxy)phenoxy-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-amino-6-trifluoromethylphenoxy)-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-amino-6-fluorophenoxy)-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-amino-6-methylphenoxy)-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-amino-6-cyanophenoxy)-α,α-dimethylbenzyl]benzene, 3,3'-diamino-4,4' -Diphenoxybenzophenone, 4,4'-diamino-5,5'-diphenoxybenzophenone, 3,4'-diamino-4,5'-diphenoxybenzophenone, 3,3'-diamino-4-phenoxybenzophenone, 4,4'-diamino-5-phenoxybenzophenone, 3,4'-diamino-4-phenoxybenzophenone, 3,4'-diamino-5'-phenoxybenzophenone, 3,3'-diamino-4,4'-dibiphenoxybenzophenone, 4,4'-diamino-5,5'-dibiphenoxybenzophenone, 3,4'-diamino-4,5 '-Diamino-4-biphenoxybenzophenone, 3,3'-diamino-4-biphenoxybenzophenone, 4,4'-diamino-5-biphenoxybenzophenone, 3,4'-diamino-4-biphenoxybenzophenone, 3,4'-diamino-5'-biphenoxybenzophenone, 1,3-bis(3-amino-4-phenoxybenzoyl)benzene, 1,4-bis(3-amino-4-phenoxybenzoyl)benzene, 1,3-bis(4-amino-5-phenoxybenzoyl)benzene, 1,4-bis(4-amino-5-phenoxybenzoyl)benzene, 1,Examples of the aromatic diamines include 3-bis(3-amino-4-biphenoxybenzoyl)benzene, 1,4-bis(3-amino-4-biphenoxybenzoyl)benzene, 1,3-bis(4-amino-5-biphenoxybenzoyl)benzene, 1,4-bis(4-amino-5-biphenoxybenzoyl)benzene, 2,6-bis[4-(4-amino-α,α-dimethylbenzyl)phenoxy]benzonitrile, and aromatic diamines in which some or all of the hydrogen atoms on the aromatic ring of the aromatic diamine are substituted with halogen atoms, alkyl or alkoxy groups having 1 to 3 carbon atoms, cyano groups, or halogenated alkyl or alkoxy groups having 1 to 3 carbon atoms in which some or all of the hydrogen atoms of the alkyl or alkoxy groups are substituted with halogen atoms.
[0031] Examples of the aliphatic diamines include 1,2-diaminoethane, 1,4-diaminobutane, 1,5-diaminopentane, 1,6-diaminohexane, and 1,8-diaminooctane. Examples of the alicyclic diamines include 1,4-diaminocyclohexane, 4,4'-methylenebis(2,6-dimethylcyclohexylamine), and the like. The total amount of diamines other than aromatic diamines (aliphatic diamines and alicyclic diamines) is preferably 20% by mass or less of the total diamines, more preferably 10% by mass or less, and even more preferably 5% by mass or less. In other words, aromatic diamines are preferably 80% by mass or more of the total diamines, more preferably 90% by mass or more, and even more preferably 95% by mass or more.
[0032] The polyimide resin in the present invention may be preferably transparent depending on the application. Examples of the acid component used in the synthesis of the precursor include 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,4,5-cyclopentanetetracarboxylic dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride, bicyclo[2,2,1]heptane-2,3,5,6-tetracarboxylic dianhydride, bicyclo[2,2,2]octane-2,3,5,6-tetracarboxylic dianhydride, 3,3',4,4'-bicyclohexyltetracarboxylic dianhydride, and 1,2,4-cyclohexanetricarboxylic dianhydride, and particularly preferred are 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride, and 3,3',4,4'-bicyclohexyltetracarboxylic dianhydride. These aliphatic carboxylic acids may be used alone or in combination of two or more. On the other hand, those containing unsaturated bonds such as bicyclo[2,2,2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride are not preferred because they tend to discolor during heat treatment and deteriorate the optical properties of the film.
[0033] Examples of the diamine component used in the synthesis of the polyimide resin or its precursor of the present invention include 1,3-phenylenediamine, 1,4-phenylenediamine, 2,4-diaminotoluene, 2,6-diaminotoluene, 3,4-diaminotoluene, 4,5-dimethyl-1,2-phenylenediamine, 2,5-dimethyl-1,4-phenylenediamine, 2,6-dimethyl-1,4-phenylenediamine, 2,3,5,6-tetramethyl-1,4-phenylenediamine, 3-aminobenzylamine, m-xylylenediamine, p -Xylylenediamine, 1,5-diaminonaphthalene, 2,2'-dimethylbiphenyl-4,4'-diamine, 2,2'-bis(trifluoromethyl)benzidine, 3,3'-dimethoxybenzidine, 4,4'-diaminooctafluorobiphenyl, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 4,4'-methylenebis(2,6-diethylaniline), 4,4'-methylenebis(2-ethyl-6-methylaniline), 4,4'-ethylenedianiline, 4,4'-diamino aminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl ether, 2,2'-bis(trifluoromethyl)-4,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-diamino-3,3'-dimethyldiphenyl methacrylate , bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, 2,2-bis(4-aminophenyl)hexafluoropropane, 2,2-bis(3-aminophenyl)hexafluoropropane, 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 2,2'-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis(3-amino-4-methylphenyl)hexafluoropropane, α,α'-bis(4-aminophenyl)-1,Examples of aromatic diamines include 4-diisopropylbenzene, bis(2-aminophenyl)sulfide, bis(4-aminophenyl)sulfide, 3,3'-diaminodiphenylsulfone, 4,4'-diaminodiphenylsulfone, 4,4'-diaminodiphenylsulfide, 4,4'-diaminobenzophenone, 3,3'-diaminobenzophenone, 4,4'-diaminobenzanilide, 1,4-bis(4-aminophenoxy)benzene, bis(4-aminophenyl)terephthalate, 2,7-diaminofluorene, and 9,9-bis(4-aminophenyl)fluorene. Aliphatic diamines include 1,3-diaminocyclohexane, 1,4-diaminocyclohexane, 1,3-bis(aminomethyl)cyclohexane, 1,1-bis(4-aminophenyl)cyclohexane, 4,4'-diaminodicyclohexylmethane, 4,4'-methylenebis(2-methylcyclohexylamine), 4,4'-methylenebis(2,6-dimethylcyclohexylamine), 4,4'-diaminodicyclohexylpropane, and bicyclo[2.2.1]heptane-2,3-diamine. , bicyclo[2.2.1]heptane-2,5-diamine, bicyclo[2.2.1]heptane-2,6-diamine, bicyclo[2.2.1]heptane-2,7-diamine, 2,3-bis(aminomethyl)-bicyclo[2.2.1]heptane, 2,5-bis(aminomethyl)-bicyclo[2.2.1]heptane, 2,6-bis(aminomethyl)-bicyclo[2.2.1]heptane, 3(4),8(9)-bis(aminomethyl)tricyclo[5.2.1.0(2,6)]decane, and the like. Among these, particularly preferred are p-phenylenediamine, 2,2'-dimethylbiphenyl-4,4'-diamine, 2,2'-bis(trifluoromethyl)benzidine, 2,2'-bis(trifluoromethyl)-4,4'-diaminodiphenyl ether, 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene, 1,4-diaminocyclohexane, 4,4'-diaminodicyclohexylmethane, 4,4'-methylenebis(2-methylcyclohexylamine), and 4,4'-methylenebis(2,6-dimethylcyclohexylamine). The above amine components may be used alone or in combination of two or more.
[0034] As the tetracarboxylic acids constituting the polyamic acid, aromatic tetracarboxylic acids (including their acid anhydrides), aliphatic tetracarboxylic acids (including their acid anhydrides), and alicyclic tetracarboxylic acids (including their acid anhydrides) that are usually used in polyimide synthesis can be used. Among them, aromatic tetracarboxylic acid anhydrides and alicyclic tetracarboxylic acid anhydrides are preferred, aromatic tetracarboxylic acid anhydrides are more preferred from the viewpoint of heat resistance, and alicyclic tetracarboxylic acids are more preferred from the viewpoint of light transmittance. When these are acid anhydrides, the anhydride structure may be one or two in the molecule, but preferably has two anhydride structures (dianhydrides). The tetracarboxylic acids may be used alone or in combination of two or more.
[0035] Examples of alicyclic tetracarboxylic acids include alicyclic tetracarboxylic acids such as cyclobutane tetracarboxylic acid, 1,2,4,5-cyclohexane tetracarboxylic acid, and 3,3',4,4'-bicyclohexyl tetracarboxylic acid, and their acid anhydrides. Among these, dianhydrides having two anhydride structures (e.g., cyclobutane tetracarboxylic dianhydride, 1,2,4,5-cyclohexane tetracarboxylic dianhydride, and 3,3',4,4'-bicyclohexyl tetracarboxylic dianhydride) are preferred. The alicyclic tetracarboxylic acids may be used alone or in combination of two or more. When transparency is important, the alicyclic tetracarboxylic acids preferably account for, for example, 80 mass % or more of the total tetracarboxylic acids, more preferably 90 mass % or more, and further preferably 95 mass % or more.
[0036] The aromatic tetracarboxylic acid is not particularly limited, but is preferably a pyromellitic acid residue (i.e., one having a structure derived from pyromellitic acid), and more preferably an acid anhydride thereof. Examples of such aromatic tetracarboxylic acids include pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-oxydiphthalic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propanoic anhydride, etc. When heat resistance is important, the aromatic tetracarboxylic acids preferably account for, for example, 80 mass % or more of the total tetracarboxylic acids, more preferably 90 mass % or more, and further preferably 95 mass % or more.
[0037] The polyimide film of the present invention has a glass transition temperature of 250° C. or higher, preferably 300° C. or higher, and more preferably 350° C. or higher, and preferably has no glass transition point observed in the range of 500° C. or lower. The glass transition temperature in the present invention is determined by differential scanning calorimetry (DSC).
[0038] The linear expansion coefficient (CTE) of the polyimide film of the present invention is preferably -5 ppm / K to +20 ppm / K, more preferably -5 ppm / K to +15 ppm / K, and even more preferably 1 ppm / K to +10 ppm / K. When the CTE is in the above range, the difference in linear expansion coefficient with a general support can be kept small, and peeling between the polyimide film and the support made of an inorganic material can be avoided even when subjected to a process in which heat is applied. In addition, the linear expansion coefficient of the polyimide film in the present invention in question is an average value between 30 and 200°C, but the temperature range of interest varies depending on the application. When considering a process at high temperatures, a range of 30°C to 400°C is examined, or a range of 100°C to 400°C may be examined. When considering a reflow process, a range of 50°C to 280°C is examined, and a range of -50°C to 150°C may be emphasized as the operating temperature range.
[0039] The breaking strength of the polyimide film in the present invention is 60 MPa or more, preferably 120 MPa or more, and more preferably 240 MPa or more. There is no upper limit to the breaking strength, but it is practically less than about 1000 MPa. Here, the breaking strength of the polyimide film refers to the average value in the length direction and width direction of the polyimide film.
[0040] The thickness unevenness of the polyimide film in the present invention is preferably 20% or less, more preferably 12% or less, even more preferably 7% or less, and particularly preferably 4% or less. If the thickness unevenness exceeds 20%, it tends to be difficult to apply to narrow parts. The thickness unevenness of the film can be calculated, for example, by using a contact type film thickness meter to randomly select about 10 positions from the film to be measured and measure the film thickness, based on the following formula. Film thickness unevenness (%) = 100 x (maximum film thickness - minimum film thickness) ÷ average film thickness
[0041] The polyimide film in the present invention is preferably obtained in the form of a long polyimide film having a width of 300 mm or more and a length of 10 m or more that is wound up during production, and more preferably in the form of a roll-like polyimide film wound around a winding core.
[0042] In the polyimide film, in order to ensure the handling property and productivity, it is preferable to add or contain a lubricant (particles) in the film and impart fine irregularities to the polyimide film surface to ensure the lubricity. The lubricant (particles) is preferably a fine particle made of an inorganic material, and particles made of metal, metal oxide, metal nitride, metal carbide, metal acid salt, phosphate, carbonate, talc, mica, clay, other clay minerals, etc. can be used. Preferably, metal oxides, phosphates, and carbonates such as silicon oxide, calcium phosphate, calcium hydrogen phosphate, calcium dihydrogen phosphate, calcium pyrophosphate, hydroxyapatite, calcium carbonate, and glass filler can be used. The lubricant may be one type only or two or more types.
[0043] The volume average particle diameter of the lubricant (particles) is usually 0.001 to 10 μm, preferably 0.03 to 2.5 μm, more preferably 0.05 to 0.7 μm, and even more preferably 0.05 to 0.3 μm. The volume average particle diameter is based on a measured value obtained by a light scattering method. If the particle diameter is smaller than the lower limit, industrial production of the polyimide film becomes difficult, and if it exceeds the upper limit, the surface unevenness becomes too large, weakening the adhesion strength and causing practical problems.
[0044] The amount of the lubricant added is 0.02 to 50% by mass, preferably 0.04 to 3% by mass, and more preferably 0.08 to 1.2% by mass, based on the amount of the polymer component in the polyimide film. If the amount of the lubricant added is too small, the effect of the lubricant addition is difficult to expect, and the lubricating property is not sufficiently secured, which may cause problems in the production of the polyimide film, while if the amount is too large, the surface unevenness of the film becomes too large, which may cause problems such as a decrease in smoothness even if the lubricating property is secured, a decrease in the breaking strength and breaking elongation of the polyimide film, and an increase in CTE.
[0045] When a lubricant (particles) is added to or contained in a polyimide film, a single-layer polyimide film in which the lubricant is uniformly dispersed may be used, but a polyimide film with a lubricant concentration gradient may also be used, for example, in which one side is made of a polyimide film containing a lubricant, and the other side is made of a polyimide film that does not contain a lubricant or contains a small amount of lubricant. In such a film with a lubricant concentration gradient, fine irregularities are imparted to the surface of one layer (film), ensuring slipperiness in the layer (film), and ensuring good handling properties and productivity.
[0046] In the case of a film produced by a melt-stretching film-forming method, the lubricant concentration-gradient polyimide film can be obtained, for example, by first forming a film using a polyimide film raw material that does not contain a lubricant, and then coating at least one side of the film with a resin layer containing a lubricant during the process. Of course, the opposite can also be done by forming a film using a polyimide film raw material that contains a lubricant, and then coating a polyimide film raw material that does not contain a lubricant during the process or after the film formation is completed to obtain a film. The same can be said for polyimide films obtained by a solution casting method, such as polyimide films. For example, as a polyamic acid solution (polyimide precursor solution), a polyamic acid solution containing a lubricant (preferably with an average particle size of about 0.05 to 2.5 μm) in an amount of 0.02 mass % to 50 mass % (preferably 0.04 to 3 mass %, more preferably 0.08 to 1.2 mass %) based on the polymer solid content in the polyamic acid solution, and two types of polyamic acid solutions containing no lubricant or containing only a small amount of lubricant (preferably less than 0.02 mass %, more preferably less than 0.01 mass % based on the polymer solid content in the polyamic acid solution) can be used to produce the film.
[0047] The method for forming the lubricant concentration gradient polyimide film (lamination) is not particularly limited as long as it does not cause any problems in adhesion between the two layers and can be achieved without the intervention of an adhesive layer or the like. In the case of polyimide films, examples of the methods include i) a method in which one polyimide film is produced, and then a solution of the other polyamic acid is continuously applied onto the polyimide film to imidize it, ii) a method in which one polyamic acid solution is cast to produce a polyamic acid film, and then a solution of the other polyamic acid is continuously applied onto the polyamic acid film to imidize it, iii) a method using co-extrusion, and iv) a method in which a polyamic acid solution containing a large amount of lubricant is spray-coated, T-die-coated, or the like, onto a film formed from a polyamic acid solution containing no or a small amount of lubricant, and then imidized. In the present invention, the above methods i) to ii) are preferably used.
[0048] The thickness ratio of each layer in the polyimide film with a lubricant concentration gradient is not particularly limited, but assuming that the polymer layer containing a large amount of lubricant is layer (a) and the polymer layer containing no lubricant or with a small amount of lubricant is layer (b), the ratio of layer (a) / layer (b) is preferably 0.05 to 0.95. If the ratio of layer (a) / layer (b) exceeds 0.95, the smoothness of layer (b) tends to be lost, while if it is less than 0.05, the effect of improving the surface characteristics is insufficient and the slipperiness may be lost.
[0049] <Surface activation treatment of polyimide film> The polyimide film used in the present invention is preferably subjected to a surface activation treatment, which modifies the polyimide film surface to a state in which functional groups are present (a so-called activated state), thereby improving the affinity for the silane coupling agent. The surface activation treatment in the present invention is a dry or wet surface treatment. As the dry treatment in the present invention, a treatment in which the surface is irradiated with active energy rays such as ultraviolet rays, electron beams, and X-rays, corona treatment, vacuum plasma treatment, atmospheric pressure plasma treatment, flame treatment, Itro treatment, etc. can be used. As the wet treatment, a treatment in which the film surface is brought into contact with an acid or alkali solution can be exemplified. The surface activation treatment preferably used in the present invention is a plasma treatment, and a combination of a plasma treatment and a wet acid treatment.
[0050] The plasma treatment is not particularly limited, but includes RF plasma treatment in a vacuum, microwave plasma treatment, microwave ECR plasma treatment, atmospheric pressure plasma treatment, corona treatment, etc., and also includes fluorine-containing gas treatment, ion implantation treatment using an ion source, treatment using the PBII method, flame treatment by exposure to thermal plasma, ITO treatment, etc. Among these, RF plasma treatment in a vacuum, microwave plasma treatment, and atmospheric pressure plasma treatment are preferred.
[0051] As suitable conditions for plasma treatment, it is desirable to use plasmas known to have a high chemical etching effect, such as oxygen plasma, fluorine-containing plasmas such as CF4 and C2F6, or plasmas such as Ne, Ar, Kr, and Xe, which have a high physical etching effect by applying physical energy to the polymer surface. It is also preferable to add plasmas such as CO2, CO, H2, N2, NH4, and CH4, as well as mixed gases of these, and water vapor. In addition to these, it is necessary to create a plasma containing at least one component selected from the group consisting of OH, N2, N, CO, CO2, H, H2, O2, NH, NH2, NH3, COOH, NO, NO2, He, Ne, Ar, Kr, Xe, CH2O, Si(OCH3)4, Si(OC2H5)4, C3H7Si(OCH3)3, and C3H7Si(OC2H5)3, either as a gas or as a decomposition product in the plasma. When aiming for short-time processing, it is desirable to use plasma with high energy density, high kinetic energy of ions in the plasma, and high number density of active species, but since surface smoothness is required, there is a limit to how much energy density can be increased. When oxygen plasma is used, surface oxidation progresses, which is good in terms of generating OH groups, but it is likely to create a surface that already has poor adhesion to the film itself, and the surface roughness increases, so adhesion also deteriorates. In addition, when using plasma with Ar gas, the surface is affected by purely physical collisions, which also results in large surface roughness. Considering all of this, microwave plasma treatment, microwave ECR plasma treatment, plasma irradiation using an ion source that can easily implant high-energy ions, and the PBII method are also desirable.
[0052] Such surface activation treatment cleans the polymer surface and generates active functional groups, which bond with the coupling agent layer through hydrogen bonding or chemical reaction, enabling the polyimide film layer and the coupling agent layer to be firmly bonded together. The plasma treatment can also have the effect of etching the polyimide film surface. In particular, in polyimide films containing a relatively large amount of lubricant particles, protrusions due to the lubricant may hinder the adhesion between the film and the inorganic substrate. In this case, the polyimide film surface is thinly etched by the plasma treatment to expose some of the lubricant particles, and then the film is treated with hydrofluoric acid to remove the lubricant particles near the film surface.
[0053] Surface activation treatment may be performed on only one side of the polyimide film, or on both sides. When performing plasma treatment on one side, by placing the polyimide film on one side of the electrode in plasma treatment with parallel plate electrodes, plasma treatment can be performed only on the side of the polyimide film that is not in contact with the electrode. Plasma treatment can also be performed on both sides by placing the polyimide film in a state where it is electrically floating in the space between two electrodes. One-sided treatment is also possible by performing plasma treatment with a protective film attached to one side of the polyimide film. Note that PET film or olefin film with adhesive can be used as the protective film.
[0054] <Surface roughness of polyimide film> The surface roughness Ra of the polyimide film in the present invention is preferably 70 nm or less, more preferably 30 nm or less, and even more preferably 1.5 nm or less. If Ra is greater than 70 nm, it may cause uneven coating of the silane coupling agent and uneven peeling when multiple polyimide films are bonded together via a silane coupling agent layer.
[0055] <Film lamination method> In the present invention, polyimide films are laminated via a silane coupling agent layer to obtain a polyimide film laminate in which polyimide film layers and silane coupling agent condensate layers are laminated alternately. The polyimide film is laminated by stacking the polyimide films so that the surface treated with the silane coupling agent is positioned between the polyimide film layers, and then applying pressure. A combination of pressure and heat is effective. The pressure treatment may be performed, for example, by pressing, laminating, roll laminating, or the like under atmospheric pressure or in a vacuum while heating. A method of pressing and heating in a flexible bag can also be applied. From the viewpoint of improving productivity and reducing processing costs brought about by high productivity, pressing or roll laminating under atmospheric pressure is preferred, and a method using a roll (roll lamination, etc.) is particularly preferred.
[0056] In the present invention, a polyimide film laminate is obtained by laminating, by hot pressing, a polyimide film having a thermoplastic polyimide coated on one side, or a polyimide film having been subjected to an easy-adhesion treatment such as a plasma treatment. The pressure treatment may be carried out, for example, under atmospheric pressure or in a vacuum by pressing, laminating or roll laminating while heating.
[0057] The pressure during the pressure treatment is preferably 1 MPa to 30 MPa, and more preferably 3 MPa to 10 MPa. If the pressure is too high, the support may be damaged, and if the pressure is too low, there may be some areas that do not adhere, resulting in insufficient adhesion. The temperature during the pressure treatment is within a range that does not exceed the heat resistance temperature of the polyimide film used. In the case of a non-thermoplastic polyimide film, the treatment is preferably performed at 10°C to 400°C, and more preferably 150°C to 350°C. The pressure treatment can be carried out under atmospheric pressure as described above, but in order to obtain a stable adhesive strength over the entire surface, it is preferable to carry out the treatment under vacuum. The degree of vacuum produced by a normal oil rotary pump is sufficient, and a vacuum of about 10 Torr or less is sufficient. As for equipment that can be used for pressure and heat treatment, for example, the "11FD" manufactured by Imoto Manufacturing Co., Ltd. can be used for pressing in a vacuum, and for vacuum lamination using a roll-type film laminator in a vacuum or a film laminator that applies pressure to the entire surface of the glass at once using a thin rubber film after creating a vacuum, for example, the "MVLP" manufactured by Meiki Manufacturing Co., Ltd. can be used.
[0058] The adhesive strength between the polyimide film layers of the polyimide film laminate of the present invention is 0.1 N / cm or more and 20 N / cm or less, preferably 0.1 N / cm or more and 18 N / cm or less, and more preferably 0.15 N / cm or more and 15 N / cm or less, as measured by the 90-degree peeling method. EXAMPLES
[0059] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. The physical properties in the following examples were evaluated as follows.
[0060] <Compression test of stiffener> A compression test was carried out using the following equipment and conditions. Device name: Minebea TGI-50kN Measurement temperature; room temperature Compression speed: 0.2mm / min and 10mm / min atmosphere; atmosphere Measurement sample size: 30cm x 30cm For the measurement, a cage-type jig, a stage for placing the stiffener, and a compression rod (made of SUS, indenter area 10 mm x 10 mm) were used.
[0061] From the results of the compression test, the stress-strain curve of the stiffener was plotted with the horizontal axis representing compressive strain and the vertical axis representing compressive stress, and the transition point where the stress-strain curve entered the linear region was determined. The transition starting point in the present invention is the strain value at the point where the extension of the slope of the initial region where strain application begins intersects with the extension of the linear region according to Hooke's law in the stress-strain curve, as shown in Figures 7 and 8. In this test, if the strain value at the transition point where the stress-strain curve starts to transition to the linear region is 20% or less of the stiffener thickness, it means that there is no major defect in the part where the indenter comes into contact. If there is a major defect, the interval from the beginning of the stress application to the transition to the linear region of the stress-strain curve will widen, and the amount of strain at the transition point will be 20% or more of the stiffener thickness. A major defect here refers to a blister defect or a defect that can become the starting point of destruction when the stiffener is used as a reinforcing material.
[0062] In this test, the compression speed was changed to 10 mm / min and 0.2 mm / min, and the stress-strain curve was obtained. The compressive stress σ at the strain where the stress was maximum was 10 and σ 0.2 The difference is |σ 10- σ 0.2 |<0.15×σ 0.2 This means that the amount of fracture strain does not change significantly even if the rate at which compressive stress is applied changes. Here, the compressive stress at the time of the strain at which the stress is maximum is the breaking point stress in FIG. 7 or the yield point stress in FIG. 8. When it is assumed that the stiffener of the present invention is used as a reinforcing material for a connector part, a bending of about 90° may occur in the handling process at the boundary between the part joined to the metal part and the part not joined. This bending is not always at a constant speed, but varies depending on the process. Since a compressive stress occurs in the bent stiffener in the thickness direction, the fact that the breaking point stress or yield point stress does not change significantly depending on the compression speed indicates that the stiffener is not easily broken at the joint part.
[0063] 90 degree method adhesive strength The adhesive strength between the polyimide film layers of the polyimide film laminate was determined according to the 90-degree peeling method of JIS K6854-1. Device name: Shimadzu Autograph AG-IS Measurement temperature; room temperature Peel speed: 50mm / min Atmosphere: 25℃ 60%RH normal pressure air Measurement sample width: 1cm The sample was a square polyimide film laminate with sides of 100 mm, with a cut made in the surface to a depth equivalent to 120% of the thickness of the outermost polyimide film, and the outermost polyimide film was peeled off from an edge of the laminate for measurement. The adhesive strength was measured after heat treatment at 200° C. for 1 hour.
[0064] 60° bending test In the atmosphere at 25℃ and 60% RH, under normal pressure, the stiffener cut to a width of 1 cm and a length of 10 cm was placed on a work table as shown in Figure 4, and a position 3 cm from the end of the stiffener was pressed down with a 10 mm thick iron plate that was finished so that the corner R on the side that touches the stiffener is 0.3 mm. The part protruding from the iron plate was lifted so that the angle between the work table and the stiffener was 60°, and the operation of holding it for 3 seconds and releasing it was repeated 10 times. After that, the bent part was observed at 100x magnification using a Keyence VH-Z100R digital microscope to confirm the presence or absence of cracks. The cracks referred to here are scratches or cracks that reach 1 / 4 or more of the thickness of the stiffener used in the test.
[0065] [Production Example] (Preparation of polyamic acid solution) After replacing the atmosphere inside a reaction vessel equipped with a nitrogen inlet tube, a thermometer, and a stirrer with nitrogen, 223 parts by mass of 5-amino-2-(p-aminophenyl)benzoxazole (DAMBO) and 4,416 parts by mass of N,N-dimethylacetamide were added and completely dissolved, and then 217 parts by mass of pyromellitic dianhydride (PMDA) and a dispersion obtained by dispersing colloidal silica in dimethylacetamide as a lubricant (Nissan Chemical Industries, Ltd.'s "Snowtex (registered trademark) DMAC-ST30") were added so that silica (lubricant) accounted for 0.12% by mass of the total polymer solids in the polyamic acid solution, and the mixture was stirred for 24 hours at a reaction temperature of 25°C to obtain a brown, viscous polyamic acid solution V1. (Preparation of polyamic acid solution) After replacing the atmosphere in a reaction vessel equipped with a nitrogen inlet tube, a thermometer, and a stirring rod with nitrogen, 205.8g (0.480mol) of 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene and 1200g of N,N-dimethylacetamide were charged and dissolved in the reaction vessel under a nitrogen atmosphere, and 93.8g (0.478mol) of cyclobutanetetracarboxylic dianhydride was added in portions as a solid while cooling the reaction vessel, and the mixture was stirred at room temperature for 12 hours. After that, 1.0g (5.9mmol) of 4-methylcyclohexane-1,2-dicarboxylic anhydride was added and stirred for 4 hours, and then the mixture was diluted with 1000g of N,N-dimethylacetamide to obtain a polyamic acid solution V2 with a reduced viscosity of 5.28dl / g. A solution of colloidal silica microparticles having an average particle size of 0.08 μm dispersed in N,N-dimethylacetamide was added to polyamic acid solution V2, which had an amine terminal amount of 5 eq / t, so that the microparticles accounted for 2.0 mass % of the polyamic acid, to obtain microparticle-containing polyamic acid solution V2'.
[0066] (Preparation of polyimide film) The polyamic acid solution V1 obtained above was applied using a slit die onto the smooth surface (lubricant-free surface) of a long polyester film ("A-4100" manufactured by Toyobo Co., Ltd.) having a width of 1,050 mm, so that the final film thickness (film thickness after imidization) was 40 μm. The film was then dried at 105° C. for 20 minutes and then peeled off from the polyester film to obtain a self-supporting polyamic acid film having a width of 920 mm. After the polyamic acid film was obtained as described above, it was heat-treated using a pin tenter (first stage: 150°C x 5 minutes, second stage: 220°C x 5 minutes, third stage: 495°C x 10 minutes) to imidize it, and the pin-held portions on both ends were slit to obtain a long polyimide film F1 (1000 m roll) with a width of 850 mm.
[0067] (Preparation of polyimide film) The fine particle-containing polyamic acid solution V2' was applied to a polyester film having a thickness of 188 μm using a comma coater so that the final dry thickness would be 3 μm, and then the polyamic acid solution V2 was continuously extruded from a slit of a T-die on top of the applied solution so that the final dry thickness would be 40 μm to form a thin film. Both polymer solutions were supplied after a degassing process and a filtration process in which the solution was passed through a polymer filter with a filtration accuracy of 3 μm. This thin film was heated at 110°C to 135°C for 15 minutes, and then peeled off from the support to obtain a self-supporting film with a volatile component content of 23.7% by mass.
[0068] Next, both ends of this self-supporting film were held by a film holding device attached to a chain driven along a rail, and the film was inserted into a continuous heating furnace heated to 150°C to 320°C, where it was heat-treated under conditions that the treatment at the highest temperature in the furnace was for 5 minutes or less. The oxygen concentration in the furnace at that time was 20.6%. By the above process, imidization was completed with the amount of volatile components being 1 mass% or less, and a long polyimide film F2 (200 m roll) with a thickness of 40 μm was obtained.
[0069] In addition to these, commercially available heat-resistant films were also used in the examples and comparative examples. F3: Upilex 75S (polyimide film manufactured by Ube Industries, Ltd., thickness 75 μm)
[0070] <Vacuum plasma treatment of polyimide film> As a pre-process for the silane coupling agent treatment on the polyimide film, the polyimide film was subjected to vacuum plasma treatment. For the vacuum plasma treatment, a metal mask was placed on the silane coupling agent-treated surface of the glass and set in the device, the vacuum chamber was evacuated to 1x10-3 Pa or less, argon gas was introduced into the vacuum chamber, and the glass plate surface was subjected to argon gas plasma treatment for 20 seconds under the conditions of a discharge power of 100 W and a frequency of 15 kHz.
[0071] <Silane coupling agent treatment 1> Using the device for generating silane coupling agent vapor, the outline of which is shown in FIG. 5, the silane coupling agent was applied to the polyimide film under the following conditions. A container containing 100 g of a silane coupling agent (KBM-903: 3-aminopropyltrimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd.) was adjusted to a temperature of 40°C, and nitrogen gas was then supplied in a bubbling manner at 20 L / min. The nitrogen gas containing the generated silane coupling agent vapor was introduced into the chamber through piping, and both sides of the polyimide film were exposed to the gas for 3 minutes to obtain a silane coupling agent-coated polyimide film (40 cm x 40 cm).
[0072] <Silane coupling agent treatment example 2> Using the device for generating silane coupling agent vapor, the outline of which is shown in FIG. 6, the silane coupling agent was applied to the polyimide film under the following conditions. A polyimide film with a width of 350 mm was passed through a chamber with dimensions of 750 mm x 200 mm x 400 mm and a slit with dimensions of 20 mm x 370 mm at a speed of 240 mm / min. A container containing 100 g of a silane coupling agent (Shin-Etsu Chemical Co., Ltd.'s "KBM-903": 3-aminopropyltrimethoxysilane) was adjusted to 40°C, and nitrogen gas was sent in a bubbling manner at 20 L / min, and the nitrogen gas containing the generated silane coupling agent vapor was introduced into the chamber through a pipe, and both sides of the polyimide film were exposed to the gas for 3 minutes, and immediately laminated with a second polyimide film F1 at 100 MPa to obtain a temporary adhesive body. This laminate was repeatedly placed in the unwinding section and laminated multiple times to obtain a temporary adhesive body of the desired thickness.
[0073] In the following, Example 3 and Example 6 will be read as Reference Example 1 and Reference Example 2, respectively. <Example 1> The plasma-treated polyimide film F1 is then stretched until the final thickness is 0.1 mm. Then, a release sheet is sandwiched between the layers, and the layers are vacuum pressed at 400°C and 30MPa. was applied for 60 min to create a stiffener.
[0074] <Example 2> A stiffener was produced in the same manner as in Example 1, except that the final thickness was 0.2 mm.
[0075] <Example 3> A temporary bonded body having a thickness of 0.5 mm was prepared using the polyimide film F1 by the method of Silane Coupling Agent Treatment Example 2, and was then heat-treated at 110° C. for 20 hours while wound around a PP core to prepare a stiffener.
[0076] <Example 4> Polyimide film F2 was stacked until the final thickness was 0.1 mm, and a release sheet was sandwiched between them. A stiffener was produced by applying a pressure of 30 MPa at 350° C. for 20 minutes under reduced pressure in a vacuum press.
[0077] <Example 5> A stiffener was produced in the same manner as in Example 4, except that F3 was used as the polyimide film.
[0078] <Example 6> A polyimide film with a silane coupling agent was prepared using F2 as a polyimide film and silane coupling agent treatment 1. The polyimide film with the silane coupling agent was stacked until the final thickness was 0.1 mm, and then a release sheet was sandwiched between them. A pressure of 100 Pa was applied to reduce pressure in a vacuum press to perform temporary bonding. The resulting temporary bonded laminate was then placed in a clean oven and heated at 180°C for 1 hour in a nitrogen atmosphere to obtain a stiffener. <Example 7> A stiffener was produced in the same manner as in Example 1, except that the final thickness was 1 mm.
[0079] <Comparative Example 1> A stiffener was produced in the same manner as in Example 3, except that the laminator roll was not passed during temporary bonding.
[0080] <Comparative Example 2> A stiffener was produced in the same manner as in Example 1, except that the final thickness was 0.3 mm and the pressure during pressing was 5 MPa.
[0081] The results of evaluation of the obtained laminate are shown in Table 1. In contrast to Comparative Examples 1 and 2, in which gaps occur between the layers, the stiffeners of the Examples have fewer defects, even though the same film is used. In addition, stiffeners with smaller differences in compressive stress when the compression speed is changed have high bending resistance.
[0082] [Table 1] [Industrial Applicability]
[0083] The stiffener of the present invention has no gaps between layers and has excellent bendability, and therefore can be used not only for reinforcing FPC boards but also for any application in which a polyimide stiffener may be combined with a metal member. [Explanation of symbols]
[0084] 11 Base film 12, 22, 32 adhesive layer 13 Separator 14 Flexible Printed Circuit Board 23 Copper foil 31 Polyimide film 41 Metal plate 42 Stiffener 61 Film unwinding section 62 Coating fluid supply section 63 Coating fluid discharge section 64 Exhaust port for coating fluid vapor 65 Long substrate unwinding section 66 Pressurizing section 67 Winding section 68 Height adjustment roll for long substrates
Claims
1. A stiffener having two or more layers of polyimide film laminated therein (excluding polyimide laminates having a structure in which multiple polyimide film layers and silane coupling agent condensate layers are alternately stacked), the stiffener has a thickness of 0.1 mm to 1 mm; A stiffener characterized in that when a compression test in the thickness direction is performed at a compression speed of 0.2 mm / min using a rod whose contact surface with the stiffener is 10 mm x 10 mm, the number of locations that do not satisfy the following condition (I) is 0.1 or less per square centimeter. Condition (I) In a stress-strain curve of the stiffener, obtained with the horizontal axis representing compressive strain and the vertical axis representing compressive stress, the strain value at the transition start point where the stress-strain curve transitions to a linear region is 20% or less of the stiffener thickness.
2. 2. The stiffener according to claim 1, characterized in that, when a compression test is conducted in the thickness direction using a rod having a contact surface with the stiffener of 10 mm x 10 mm, the stiffener satisfies the following condition (II): Condition (II) In the stress-strain curve of the stiffener obtained with the compression speed set at 10 mm / min and 0.2 mm / min, the horizontal axis is the compressive strain, and the vertical axis is the compressive stress, the difference between the compressive stress σ10 and σ0.2 at the strain where the stress is maximum is |σ10−σ0.2|<0.15×σ0.2 It is.
3. 2. The stiffener according to claim 1, characterized in that it has a thickness of 0.2 mm or less, and when the operation of bending the stiffener at an angle of 60° along an iron plate placed on top, holding the bending for 3 seconds, and releasing the bending is repeated 10 times, no cracks are generated in the bent portion.
Citation Information
Patent Citations
Flexible printed wiring board
JP2019212713A
stiffener
WO2019135367A1